Workshop on Proposal and Classroom Action Research Report for Primary School Teachers in Pasaman District, West Sumatera - Relsas Yogica (Pelita Eksakta, 2019)
Classroom action research has the character to find and solve problems in the learning process. By conducting action researchs the ability of teachers to master classroom conditions will increase, so that students' understanding of material will increase. Further impact, students' interest in learning will increase rapidly. But there are still many teachers who are unable to carry out this action research. In Pasaman District, this problem arose. Action is needed to train teachers to be able to carry out classroom action research. We have carried out community service in the form of workshops on making proposals and preparing research reports for teachers. We carry out activities for 1 month, in accordance with the agreement of the team, the school principal and the district head. The workshop was held at Pasaman 23rd Public Elementary School. Participants are teachers from several schools, as many as 40 people. The workshop instructor is a Classroom Action Research expert. Based on the satisfaction questionnaire, we learned that the workshop material had increased teacher understanding, a score of 92.24. The workshop method has trained the teacher's ability, a score of 89.66. Workshop techniques have improved the quality of learning and improved teacher skills, a score of 93.10. Finally, the workshop product has increased the teacher's understanding of classroom action research, a score of 93.10. Based on these data it was concluded that the overall workshop implementation had improved teacher competency.